2023
DOI: 10.1186/s12920-023-01581-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for causal effects of polycystic ovary syndrome on oxidative stress: a two-sample mendelian randomisation study

Abstract: Background Polycystic ovary syndrome (PCOS) is often accompanied by increased oxidative stress levels; however, it is still unclear whether PCOS itself is causally related to oxidative stress (OS), whether OS can increase the occurrence of PCOS, and which characteristics of PCOS increase OS levels. Therefore, this study explored the causal relationship between PCOS, its characteristics, and OS. Methods Two-sample bidirectional and two-sample Mendel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We select 11 OS biomarkers from diverse categories. First, as endogenous antioxidants are highly responsive to OS [39], we use 4 enzyme antioxidants (GST, CAT, SOD, GPX) as OS injury biomarkers, which have been utilized in previous MR studies [40, 41]. One of the mechanisms through which obesity induces systemic OS is chronic inflammation [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…We select 11 OS biomarkers from diverse categories. First, as endogenous antioxidants are highly responsive to OS [39], we use 4 enzyme antioxidants (GST, CAT, SOD, GPX) as OS injury biomarkers, which have been utilized in previous MR studies [40, 41]. One of the mechanisms through which obesity induces systemic OS is chronic inflammation [34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…It’s crucial to highlight that despite the numerous similarities between PCOS and GDM, such as insulin resistance and their association with type 2 diabetes and postpartum impaired glucose metabolism ( 34 ), their relationship has been observed primarily through observational studies, lacking conclusive evidence of a causal link. Presently, there are numerous MR studies on PCOS ( 37 41 ). To the best of our knowledge, this is the initial study investigating the causal effects of PCOS and its characteristic indices on GDM.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS, a common endocrine disorder affecting women, showcases the power of genomic medicine. Recent studies have identified specific genetic variants associated with PCOS, shedding light on its multifactorial aetiology [27]. This genetic insight allows for tailored treatment approaches based on an individual's genetic predisposition, potentially optimizing therapeutic outcomes.…”
Section: The Era Of Genomic Medicine: Unraveling Genetic Complexitymentioning
confidence: 99%
“…This genetic insight allows for tailored treatment approaches based on an individual's genetic predisposition, potentially optimizing therapeutic outcomes. The genetic basis of thyroid disorders, including autoimmune conditions like Graves' disease and Hashimoto's thyroiditis, has been elucidated through genomic research [27]. Understanding the genetic susceptibility of patients can guide therapeutic choices, such as the selection of antithyroid drugs or the consideration of thyroidectomy.…”
Section: The Era Of Genomic Medicine: Unraveling Genetic Complexitymentioning
confidence: 99%